1995
DOI: 10.1128/jb.177.13.3631-3640.1995
|View full text |Cite
|
Sign up to set email alerts
|

Localization of penicillin-binding proteins to the splitting system of Staphylococcus aureus septa by using a mercury-penicillin V derivative

Abstract: Precise localization of penicillin-binding protein (PBP)-antibiotic complexes in a methicillin-sensitive Staphylococcus aureus strain (BB255), its isogenic heterogeneous methicillin-resistant transductant (BB270), and a homogeneous methicillin-resistant strain (Col) was investigated by high-resolution electron microscopy. A mercury-penicillin V (Hg-pen V) derivative was used as a heavy metal-labeled, electron-dense probe for accurately localizing PBPs in situ in single bacterial cells during growth. The most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Since this splitting system disappears during cell separation ( Fig. 1 D), for more than 25 years it was thought to be responsible for lytic cell separation (Giesbrecht and Wecke 1971;Paul et al 1995). According to our data obtained during induced cell separation, however, the splitting system is not involved in those muralytic processes that result in partition (Fig.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Since this splitting system disappears during cell separation ( Fig. 1 D), for more than 25 years it was thought to be responsible for lytic cell separation (Giesbrecht and Wecke 1971;Paul et al 1995). According to our data obtained during induced cell separation, however, the splitting system is not involved in those muralytic processes that result in partition (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…It has been concluded, therefore, that the splitting system is lytically degraded and released into the culture medium during cell separation (Giesbrecht et al 1976(Giesbrecht et al , 1985(Giesbrecht et al , 1992Paul et al 1995). Since subinhibitory concentrations of certain β-lactams are known to inhibit the formation of a detectable splitting system without substantially interfering with cell growth, cell division, and cell separation (Beise et al 1988), the question arose whether staphylococci would have any alternative cell-separation mechanism not involving the splitting system.…”
Section: Introductionmentioning
confidence: 98%
“…6B). Interestingly, electron microscopy experiments using labeled penicillin in S. aureus cells indicated that a fraction of the PBPs may not be bound to the plasma membrane (30). Since vitreous sections cannot be immunolabeled, targeted gene deletions or selective The layered structure of the gram-positive envelope raises questions.…”
Section: Discussionmentioning
confidence: 99%
“…This strongly suggests to us that the ring pattern is an integral part of the fabric of the new cell wall and that it most likely does not only represent structural features of the splitting system. Since new peptidoglycan is inserted at the inner face of the wall via penicillin-binding proteins (33) and since the splitting system must involve autolysins and the breakdown of peptidoglycan as the daughter cells separate, it is logical to assume that the rings are structural features or remnants of the putting in and taking out of the peptidoglycan during the division of these grampositive bacteria. For example, if the peptidoglycan strands are oriented perpendicular to the cross wall (see next paragraph), then some circular regions may have the peptidoglycan ends protrude slightly above the plane of the cross-wall while other circular regions might have the ends slightly below this plane, thus generating a landscape of circular grooves and valleys.…”
Section: Vol 186 2004 Afm Of Cell Growth and Division In S Aureus mentioning
confidence: 99%